Errors in skilled complex actions: psychological, biomechanical, and neurophysiological assessments of the yips in golf putting - Philippen, P. B. (Universität Bielefeld, 2013)
History has shown that we often learn what is right from what is wrong. To understand more about human motor control, this dissertation investigates a systematic error that occurs in complex human actions, referred to as 'the yips'. The yips has been defined as an involuntary muscle contraction that results in a jerk, tremor, or freezing of a planned movement. In golf, the yips occur most often during the putting stroke. The etiology of the yips is still unclear. It has been postulated that the yips might be a form of task-specific focal dystonia (TSFD), which is a movement disorder affecting highly trained fine-coordinated movements such as playing an instrument or writing. It is argued that typical TSFD symptoms such as abnormal postures or tremors are related to neurophysiological abnormalities. Alternatively, it has been suggested that the yips might be a severe form of choking under pressure, which is a significant drop in one's performance in situations of perceived high pressure. It is argued that choking might be caused by the adoption of a dysfunctional focus of attention during the execution of the affected movement. Currently, it is argued that the reasons for the yips reside on a continuum, with mechanisms of focal dystonia on one pole and mechanisms of choking under pressure on the other pole. The yips can be devastating for one's performance and sometimes even one's professional career. It seems that the yips are fairly widespread across highly skilled golfers; Yet, despite its prevalence and its impact on performance, there is a paucity of reliable interventions to cope with the yips in golf putting. One reason for this lack of interventions is certainly the unclear etiology of the yips. The purpose of this present dissertation is to enhance the understanding of the etiology of the yips in golf putting. This is not only crucial to eventually be able to advise yips-affected golfers on how to cope with the yips, but also will promote our general understanding of motor control, and especially its disturbances. The research in this dissertation focuses on psychological, behavioral, and physiological aspects of the yips in golf putting. Furthermore, it extends the suggestions of potential underlying reasons of the yips in golf putting. Last but not least, the dissertation provides the first scientifically developed yips-relevant diagnostic criteria and a procedure to objectively assess the yips in golf putting. More specifically, in chapter 2 the psychological components of the yips in golf are addressed. Although it has been suggested that the yips might be a form of choking, to date no investigations of the thoughts and focus of attention of yipsaffected golfers have been published. Given the importance of attention and arousal in explaining choking, we conducted an interview study to investigate the thoughts, feelings, and focus of attention in yips-affected golfers. Based on the aforementioned continuum model, we expect the yips-affected golfers to mainly focus on worries or the movement execution when having to take a putt. From the interviews, it becomes apparent that yips-affected golfers have a negative (i.e., dysfunctional) cognitive and emotional association with the task of putting (i.e., a yips-affected stroke). The results show that the golfers were predominantly occupied with negative thoughts such as perceived loss of control, loss of confidence in their putting skills, and worries about mistakes due to the yips. In addition, the feelings associated with the yips were exclusively negative, including disappointment, frustration, anger, and especially anxiety about having to take a putt. In addition to exhibiting this negative cognitive and emotional pattern, 11 of the 17 participants reported a focus on technical aspects or a focus on the yips and its negative performance outcomes. The results support the previous postulation that the yips symptoms of some golfers are related to mechanisms similar to the ones underling choking under pressure. The present study provides a possible starting point for the development and evaluation of interventions for the yips. The present categorization promotes a better understanding of how golfers experience the yips and which processes might be involved in the yips and its long-term nature. This provides practitioners with valuable information to develop effective treatment. In chapter 3, the suggestion that predominately highly skilled golfers are affected by the yips is addressed. This suggestion is one of the main reasons for the postulation that the yips might be a form of TSFD, because TSFDs usually affect highly trained skills. However, as has been pointed out above, it is not known whether relatively untrained golfers also experience the yips, because to date only professional and highly competitive golfers have been investigated. Therefore, we designed an online questionnaire to assess the prevalence of yips in golf across the entire skill range. Based on the suggestion that the yips are a form of TSFD, we expect that only highly experienced golfers are affected by the yips. The results revealed that across the entire skill range, 22.4% of golfers surveyed reported being currently affected by the yips. Furthermore, although the results show that novice golfers also report being affected by the yips, the prevalence of the yips is higher across more highly skilled golfers. In addition to the prevalence and characteristics of the yips, we also assessed which other movements are affected by yips-like symptoms. The results motivated a subsequent online inquiry, investigating the sports history of a subsample of participants from the first questionnaire. The results show that more yips-affected than unaffected golfers had played a sport that requires the interception of a ball with an object that is controlled with the hands. Since the prevalence of yips in golf is higher than the prevalence of other TSFDs, we suggest that there might be multiple causes for the same yips symptoms that have not yet been explored. Based on our results, we propose a possible relationship between the yips in golf and a certain sports history. In chapter 4, we address the behavioral and physiological components of the yips in golf putting. Specifically, we address the paucity of an objective diagnosis of the yips. We present a biomechanical analysis of the yips in golf putting to identify its physical manifestation. Using kinematic analyses, we establish the first objective diagnostic criteria to distinguish yips-affected putts from unaffected putts. The results show that the yips were provoked 100% reliably when putting the ball with the dominant hand only. Also, the yips largely disappeared when there was no ball. Moreover, kinematic analyses show that a higher maximal rotation velocity and a larger number of directional changes in the affected wrist's rotation clearly distinguished the yips-affected putts from unaffected putts. The EMG results revealed no significant differences between yips-affected and unaffected putts. Overall, the results show that putting the ball with the dominant hand only reliably provokes yips that can be measured by the wrist's rate of rotation and the number of the rotation's directional changes. This procedure allows for an accurate diagnosis of the yips in putting as well as a way of reliably provoking the yips in laboratory settings. This is especially valuable for future studies on the yips which aim to assess the effectiveness of interventions or the effect of experimental manipulations. We conclude this chapter with a revised definition of the yips in golf putting and recommendations for how to diagnose the yips in future studies, as well as on the golf course. In the concluding chapter, we discuss the current findings in the framework of a more general model of motor control and propose an alternative explanation for the causes of the yips in golf putting.